Методи структурної інженерії поверхні для вирішення завдань багатофакторного підвищення рівня експлуатаційних характеристик матеріалів - Білозеров, Валерій Володимирович; Волков, Олег Олексійович; Князєв, Сергій Анатолійович; Князєва, Ганна Олександрівна; Конотопська, Тетяна Борисівна; Краєвська, Жанна Владиславівна; Субботіна, Валерія Валеріївна; Субботін, Олександр Володимирович; Федоренко, Ганна Анатоліївна (Харківський національний автомобільно-дорожній університет, 2023)
У роботі проаналізовано методи структурної інженерії поверхні (ТФЗ, ДТФЗ, ТФЗв, МДО, PVD). Були проведені експериментальні дослідження чорних та кольорових металів. Розглянуто зміну та отримання нових властивостей у поверхневих шарах виробів.

Structural surface engineering encompasses a complex of scientific disciplines and technological methods of directed change of physical and chemical properties of materials surface layers by modification, deformation, application of films, coatings, protective layers, with the help of various combined methods. In the course of the study several different methods of structural engineering of the surface are considered for solving problems of multifactor increase of the level of exploitation characteristics of materials. The methods described in the article are characterized by different physics of the process on the way to obtaining the result, but are aimed at modifying the structure and properties of the surfaces to which they are applied. Goal. Consideration of different methods of influence on the surface of ferrous and non-ferrous alloy objects, analysis of their influence on the modification of the structural state and properties of the surface layers that were investigated, discussion of the peculiarities of each of the considered technologies.
Methods of structural surface engineering in solving problems of multifactorial improvement of materials performance
Keywords: структурна інженерія поверхні; мікродугове оксидування; анодно-катодний режим; склад електроліту; фазовий склад; рентгеноструктурний аналіз; товщина покриття; твердість; вакуумно-дугове нанесення покриттів; structural surface treatment; microarc oxidation; anodic-cathodic mode; electrolyte composition; phase composition; X-ray analysis; coating thickness; hardness; vacuum-arc coating